Recent advances in photopharmacology: Harnessing visible light‐activated azobenzene photoswitches - Yongliang Feng; Kun Zhang; Xingrui Gao; Weiwei Yang; Junya Wan; Hong‐Ru Fu; Hui Guo; Ziyong Li (Responsive Materials)
Abstract In the era of precision medicine, photopharmacology that employs molecular photoswitches offers unique opportunities to control the action of bioactive molecules with high spatiotemporal resolution, while reducing drug side effects, systemic toxicity and the emergence of resistance. Over the past two decades, the field of photopharmacology has witnessed great achievements in treating with blindness, cancer, diabetes, antibiotic resistance, and to name but a few. Several challenges remain, however, in particular the fact that most photopharmacological agents trigger their activity by Ultraviolet light, which is damaging to normal cells and has poor tissue permeability. Visible light‐activated photopharmacological agents are hence highly desirable and have captured keen recent research interest. This review highlights strategies for the synthesis of visible light‐responsive azobenzenes (ABs) and their applications in the emerging photopharmacology. Such visible light‐activated photoswitchable drugs tremendously extend the scope of photopharmacology for future in vivo applications. Furthermore, we identify the current challenges and discuss future opportunities for rational design in photopharmacology that switches at a higher wavelength. We hope to inspire further research into the photochemistry of novel photopharmacological agents based on ABs or other photoswitches, which are triggered by the excitation light in “phototherapeutic window” of 650–900 nm, ultimately enabling full realization of these “smart” drugs in the clinical practice.